Kepemimpinan Inspirational Motivation Kepala Sekolah Dalam Pembelajaran Sains Robotika Di SMA Averos Kota Sorong - Sri Akidah (Al-Riwayah : Jurnal Kependidikan, 2020)
This paper outlines the Inspirational Motivation Leadership of The Principals in learning Robotics at Averos Sorong City High School. Robotics is an excellent subject at Averos High School. In addition, Robotics Science is also an extracurricular activity for Averos high school students. Many achievements have been reached by Averos High School in robotics including the winner of the science olympiad competition, and winning the championship at the national level and some are sent to compete in the other country. This is inseparable from the leadership of the Principal of Averos High School. Therefore, it is interesting to discuss the Inspirational Motivation Leadership of Sorong City High School Senior High School. The results of this study are Robotics Science is a local subject in Averos Sorong City High School. Robotic Science in Averos High School is divided into two groups, namely robotics as a subject and robotics as club. Robotics Science Learning is given to all Class X and Class XI students. The aim of learning robotics is to improve the quality of Averos high school students. So, when they graduate from Averos they will have competitiveness in the development of science and technology. And the Principal Inspirational Motivation Leadership in Robotics Science Learning is demonstrated by caring for teachers, staff and students, involving everyone in the organization. Giving appreciation, making sure that the subject is fun, showing real trust, and listening to subordinates. While the output of robotics science was made students capable of creating Arduino Soccer-Transforter Robot in 2013, Drone in 2013, Robot Linetracer Analog 12 Sensors in 2014, Robot Wall Follower 2014, Analog Transforter Robot 2017, Miniature Wireless Bluetooth Based Home 2018, Alingu in 2018, Seven Segments in 2018, and Bluetooth Pairing Robot.